PENTINGNYA PERAN KOMUNIKASI KELUARGA DALAM MENGATASI PENYALAHGUNAAN NARKOTIKA PADA REMAJA - ENNY NURCAHYAWATI; ZULKARNAIN ALFISYAHRIN (Institut Bisnis Muhammadiyah Bekasi, 2020)
In the beginning, a high sense of curiosity, drug abuse usually occurs, especially in Indonesia, drug abuse is still very important to be discussed, especially in adolescents. Youth is the young generation of the nation's hope. However, we are still worried about the behavior of adolescents whose associations tend to lead to things that violate social and religious norms and violate the rule of law. Even to the emergence of negative behavior among adolescents such as student fights, free sex and consuming drugs. By taking drugs means they are endangering their lives and their future and destroying all hopes. Lack of parental supervision and the failure of their parental relationships causes adolescents to become trapped in deviant behavior, using drugs as a way out for them. The healing condition is on the other hand; the role of the family is very important. The research method used is an observational and descriptive analytical method using differential association theory which is used to explain criminal behavior, namely evil behavior as a person's way of life.